Real-Time Dissemination of Aggregate Data on Presentation and Outcomes of Patients With Venous Thromboembolism: The RIETE Infographics Project - Tafur, Alfonso; Bikdeli, Behnood; Weinberg, Ido; Jimenez, David; Monreal, Annia; Barba, Raquel; Mira, Enrique; Macrinici, Victor; Krumholz, Harlan M; Hawkins, Mayra; Monreal, Manuel; RIETE Investigators; et al. (SAGE Publications, 2020)
In the current era of patient empowerment and precision medicine, access to timely information is critical to decision-making. Unfortunately, we currently lack patient-specific, real-time data about clinical presentation, risk of thrombotic or hemorrhagic events, key risk factors, and adverse outcomes in patients with venous thromboembolism (VTE). Accordingly, the Registro Informatizado Enfermedad TromboEmbólica (RIETE) investigators developed a tool to provide an open-source, real-time graphic representation of VTE-related data derived from over 90 000 patients with confirmed VTE. This information is intended to facilitate discussion in the informed decision-making process. The current article describes the aims, rationale, methods, and ongoing and future efforts of the real-time VTE infographics developed by the RIETE registry collaborators.